Virtual training system using visual feedback for sport skill learning - Tanaka, K. (International Journal of Computer Science in Sport, 2009)
Recently, the number of studies on virtual environments for supporting sport skill learning has been growing. Most of the studies have focused on improving the quality of the environment created by virtual reality technology. In contrast, this study focused on the visual feedback of trainees` performances. When a trainee moves within a virtual environment shown on a display device, the trainee imagines the pictures 3-dimensionally. However, since the spatial relation between the trainee and the virtual environment cannot be filmed 3-dimensionally, it is a challenge to get visual information about the trainee`s performance fed back to the trainee effectively. This paper proposes a method which makes it possible to visualize the performance 3-dimensionally and feed back pictures using Mixed Reality technology. A virtual Karate system using the method and an experimenton the system are also described.